2007
DOI: 10.1109/acc.2007.4283070
|View full text |Cite
|
Sign up to set email alerts
|

Design and Modeling of a New Motorcycle Riding Simulator

Abstract: Abstract-This paper presents the various stages for the construction of a two wheeled riding simulator. Despite its simplicity, the particularity of this simulator comes from the possibility to reproduce most of the movements and the inertial effects allowing to perceive sensations close to reality cases. This simulator has been developed for two purposes:• as a training tool for new riders with different scenarios: normal traffic environment, dangerous riding situations (avoidance, emergency braking, nearly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 11 publications
(10 reference statements)
0
24
0
Order By: Relevance
“…A survey showed that similar works in the literature present systems that are mainly focused on human-machine interfaces, comfort characterization, and riding simulation over different scenarios, with the aim of improving road safety [1,[10][11][12][13][14][15]. They are conceived to evaluate the rider's subjective feeling or to train riders to face various situations, from normal riding to emergency manoeuvres and, except for [1], they are not able to employ a real-world motorbike.…”
Section: Introductionmentioning
confidence: 99%
“…A survey showed that similar works in the literature present systems that are mainly focused on human-machine interfaces, comfort characterization, and riding simulation over different scenarios, with the aim of improving road safety [1,[10][11][12][13][14][15]. They are conceived to evaluate the rider's subjective feeling or to train riders to face various situations, from normal riding to emergency manoeuvres and, except for [1], they are not able to employ a real-world motorbike.…”
Section: Introductionmentioning
confidence: 99%
“…A driver on the simulator handles the gas throttle and the brake lever to accelerate and slow down. Figure 10 shows the recorded acceleration profile, as well as the corresponding pitch angle calculated by the motion cueing model (for more information on the general simulation scheme and the motion cueing algorithm refer to Nehaoua et al [2007], Nehaoua et al [2006]). Fig.…”
Section: Fig 8 Constructed Riding Motorcycle Simulatormentioning
confidence: 99%
“…Unlike speed which can be reproduced with the simple visual projection, acceleration can't be felt without body excitation via a mechanical motion. Special techniques called motion cueing algorithms can transform the actual motorcycle motion in an achievable movement by the simulator, which can create an acceleration illusion without causing sensory conflict (Nehaoua et al [2007], Nehaoua et al [2006]). …”
Section: Preliminariesmentioning
confidence: 99%